Assessment of poultry process hygiene and bacterial dynamics along two broiler slaughter lines in Norway. (April 2023) - Hauge, Sigrun J.; Johannessen, Gro S.; Haverkamp, Thomas H.A.; Bjørkøy, Solfrid; Llarena, Ann Katrin; Spilsberg, Bjørn; Leithaug, Magnus; Økland, Marianne; Holthe, Janne; Røtterud, Ole-Johan; Alvseike, Ole; Nagel-Alne, Gunvor Elise
Abstract: Good process hygiene in broiler slaughter is paramount to achieve safe products with long shelf-lives. Here we investigated changes in bacterial load and diversity on chicken carcasses at selected stages on slaughtering lines in two abattoirs in Norway. Carcasses included in the study, came from flocks that had been classified as either positive or negative for Campylobacter . In total, 120 neck-skins were collected at four sampling points: before scalding, after plucking, after evisceration, and after chilling. The bacterial load was analyzed at each sampling point using quantitative and qualitative cultivation while the bacterial composition was determined using amplicon sequencing of the 16S rRNA gene. Bacterial loads on carcasses decreased along the slaughter line by 2.1, 1.1, 1.1, and 1.0 log cfu per g for Total Plate Counts (TPC), Enterobacteriaceae, Escherichia coli, and Campylobacter, respectively. The largest reduction was observed after washing and chilling. For TPC, a large reduction was also observed after scalding and plucking. Scalding water samples had low amounts of E. coli and were negative for Campylobacter . Only a weak statistical association was found between indicator counts and Campylobacter . The 16S rRNA amplicon sequencing results showed a more diverse bacterial community at the start of the slaughter line, dominated by Staphylococcus, Escherichia - Shigella, and Streptococcus, which altered to a less-diverse community, dominated by Asinibacterium spp., Afipia spp., Pseudomonas, Polaromonas, and Psychrobacter after chilling. Both abattoirs were assessed as low risk by a new categorization method. This study contributes to identify factors that increases and decreases levels of Campylobacter and other bacteria during slaughter and should enable the implementation of control measures and thus improve meat safety. Highlights: Bacterial communities were identified along the slaughter lines. Bacterial loads on broiler carcasses decreased by 1–2 log/g along slaughter lines. Air-chilling without use of water reduced Campylobacter . Scalding reduced total plate count by > 1 log/g.